2003
DOI: 10.4315/0362-028x-66.9.1611
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation, Growth, and Survival Studies of Listeria monocytogenes Strains Belonging to Three Distinct Genotypic Lineages

Abstract: Twenty-one Listeria monocytogenes strains belonging to three different genotypic lineages were evaluated for differences between lineages and between individual strains with respect to thermal inactivation, growth, and survival. Three sets of heat inactivation conditions (60°C, pH 6.0, and 0.5 M lactate; 55°C, pH 6.0, and 0.5 M lactate; and 50°C, pH 4.0, and 0.5 M lactate) were used on strains grown in modified brain heart infusion (BHI) broth with and without glucose. Two sets of growth conditions (35°C, pH 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 16 publications
9
60
1
2
Order By: Relevance
“…This result was in agreement with the result of an Escherichia coli study where the magnitude of strain variation was greater than the uncertainties calculated from experimental procedures using single strains or cocktails (Whiting and Golden, 2002). In contrast, strain variability was reported to be similar to the biological variability in another study using L. monocytogenes (De Jesús and Whiting, 2003). Similarity between strain variability and biological variability was also reported from a recent publication using Salmonella enterica strains, where the coefficient of variation (CV) of strain variability on specific inactivation rate (k heat ) was 18.3% compared to the CV among replicates of 10.2±6.5% ).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This result was in agreement with the result of an Escherichia coli study where the magnitude of strain variation was greater than the uncertainties calculated from experimental procedures using single strains or cocktails (Whiting and Golden, 2002). In contrast, strain variability was reported to be similar to the biological variability in another study using L. monocytogenes (De Jesús and Whiting, 2003). Similarity between strain variability and biological variability was also reported from a recent publication using Salmonella enterica strains, where the coefficient of variation (CV) of strain variability on specific inactivation rate (k heat ) was 18.3% compared to the CV among replicates of 10.2±6.5% ).…”
Section: Discussionsupporting
confidence: 81%
“…In both studies however, the factors reported to influence the D-value were smaller than the variability of all published data, except for the effect of high salt concentration. To date, several studies have focused on investigating the effect of strain variability on thermal resistance of vegetative cells De Jesús and Whiting, 2003;Mackey et al, 1990;Ng et al, 1969;Sörqvist, 1994) and spores (Berendsen et al, 2014;Luu-Thi et al, 2014). However, the results between studies, even those using the same species, were different.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations